2023
DOI: 10.1111/ocr.12642
|View full text |Cite
|
Sign up to set email alerts
|

Automatic landmark identification in cone‐beam computed tomography

Abstract: ObjectiveTo present and validate an open‐source fully automated landmark placement (ALICBCT) tool for cone‐beam computed tomography scans.Materials and MethodsOne hundred and forty‐three large and medium field of view cone‐beam computed tomography (CBCT) were used to train and test a novel approach, called ALICBCT that reformulates landmark detection as a classification problem through a virtual agent placed inside volumetric images. The landmark agents were trained to navigate in a multi‐scale volumetric spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In this study, we evaluated the tooth movement of all lower teeth after correcting mild to moderate malocclusion, while the literature mainly reports different evaluations and methodologies, such as the levelling of only mandibular anterior teeth, 27 assessment of severe maxillary malocclusion, 6 evaluation of maxillary canine distalization, 14 en-masse retraction utilizing miniscrews, 35 transversal tooth movement of mandibular lateral segments, 15 second molar protraction and upper canine retraction. 36 The automated AI-based dental tools used in this study are accurate 8,[19][20][21][22][23][24]26,31,32 and facilitate the assessment and quantification of tooth movement, reducing the time needed by clinicians and researchers to analyse imaging processes and evaluations by at least 90%. It is important to note that while commercial companies such as Relu, 37 Diagnocat 38 and Materialise, 39 as well as previous studies, have demonstrated similar applications, most of their tools are not integrated into the same platform and are not easily accessible due to cost and code unavailability.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we evaluated the tooth movement of all lower teeth after correcting mild to moderate malocclusion, while the literature mainly reports different evaluations and methodologies, such as the levelling of only mandibular anterior teeth, 27 assessment of severe maxillary malocclusion, 6 evaluation of maxillary canine distalization, 14 en-masse retraction utilizing miniscrews, 35 transversal tooth movement of mandibular lateral segments, 15 second molar protraction and upper canine retraction. 36 The automated AI-based dental tools used in this study are accurate 8,[19][20][21][22][23][24]26,31,32 and facilitate the assessment and quantification of tooth movement, reducing the time needed by clinicians and researchers to analyse imaging processes and evaluations by at least 90%. It is important to note that while commercial companies such as Relu, 37 Diagnocat 38 and Materialise, 39 as well as previous studies, have demonstrated similar applications, most of their tools are not integrated into the same platform and are not easily accessible due to cost and code unavailability.…”
Section: Discussionmentioning
confidence: 99%
“…This step assured an even more precise landmark placement, highlighting that continuous human interaction with clinician feedback is essential for improving the accuracy and precision of AI algorithms. 21,22 This study consists of a secondary data analysis. The CBCT scans were originally acquired with the goal of evaluating dehiscences and fenestrations in patients, without the need for an invasive procedure such as flap elevation for direct assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations